Evaluation of Advanced Nanomaterials for Cancer Diagnosis and Treatment - Nkanyiso L. Ndlovu; Wendy B. Mdlalose; Bulelwa Ntsendwana; Thomas Moyo (MDPI AG, 2024)
Cancer is a persistent global disease and a threat to the human species, with numerous cases reported every year. Over recent decades, a steady but slowly increasing mortality rate has been observed. While many attempts have been made using conventional methods alone as a theragnostic strategy, they have yielded very little success. Most of the shortcomings of such conventional methods can be attributed to the high demands of industrial growth and ever-increasing environmental pollution. This requires some high-tech biomedical interventions and other solutions. Thus, researchers have been compelled to explore alternative methods. This has brought much attention to nanotechnology applications, specifically magnetic nanomaterials, as the sole or conjugated theragnostic methods. The exponential growth of nanomaterials with overlapping applications in various fields is due to their potential properties, which depend on the type of synthesis route used. Either top-down or bottom-up strategies synthesize various types of NPs. The top-down only branches out to one method, i.e., physical, and the bottom-up has two methods, chemical and biological syntheses. This review highlights some synthesis techniques, the types of nanoparticle properties each technique produces, and their potential use in the biomedical field, more specifically for cancer. Despite the evident drawbacks, the success achieved in furthering nanoparticle applications to more complex cancer stages and locations is unmatched.